2015
DOI: 10.1108/compel-08-2014-0211
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic fields in body by wireless inductive system

Abstract: Purpose -The purpose of this paper is to calculate the induced electromagnetic fields in human body exposed to the wireless inductive charging system of electric vehicles has been conducted based on the numerical simulation. Design/methodology/approach -A homogeneous human body model is built and a representative wireless inductive charging system is used for the exposure assessment. The numerical simulation relies on finite element method with formulations in terms of the magnetic vector potential. The electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The simulated scenario has some parallels to work from the groups of Shimamoto et al and Ding et al; however, the choice of the SF‐FDTD approach allows to use more realistic models of the IPT and its environment. The spatial high‐resolution capabilities of the proposed SF‐FDTD method require using massive parallel computing capabilities of GPGPU‐accelerated high‐performance computing systems.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The simulated scenario has some parallels to work from the groups of Shimamoto et al and Ding et al; however, the choice of the SF‐FDTD approach allows to use more realistic models of the IPT and its environment. The spatial high‐resolution capabilities of the proposed SF‐FDTD method require using massive parallel computing capabilities of GPGPU‐accelerated high‐performance computing systems.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…To illustrate the human exposure, for example, in [81] it was shown that the field values deduced in the case of a homogeneous human body phantom placed near the realistic charging structure [39,40] respected the recommendations of the ICNIRP. This charging system is assumed to deliver 3 kW on a 400 V battery, which decides the distance between two coils.…”
Section: Static Analysis In Case Of a 3 Kw Powermentioning
confidence: 99%
“…The most popular WPT method, known as inductive power transfer (IPT), is based on magnetic induction. The IPT technique has achieved great success in theoretical development and industrial applications to deliver power in certain areas of applications such as powering consumer electronic devices (Hu et al , 2007), powering link for implantable medical devices (Ding et al , 2015; Hannan et al , 2014; Hannan et al , 2011), electric vehicle charging (Budhia et al , 2013) and wireless charger for robots (Park et al , 2014). However, it has some limitations.…”
Section: Introductionmentioning
confidence: 99%